STRATEGI KEPALA SEKOLAH DAN MOTIVASI GURU DALAM MEMPERTAHANKAN PRESTASI AKADEMIK SISWA DI SD HASBUNALLAH DAN SD PLUS KABUPATEN TABALONG - Rahman A.; Husnul Madihah; Agustina Rahmi (Yayasan Pendidikan Literasi Borneo, 2025)
The main focus of this research is to explore how school principals design strategies to maintain consistent academic quality, and how teachers’ motivation serves as an essential driving force in ensuring the learning process remains effective and meaningful. The study employed a qualitative method with a case study approach in two private primary schools in Tabalong Regency. Data were collected through in-depth interviews, observations, and document analysis, and then analyzed descriptively through processes of data reduction, presentation, and conclusion drawing. The findings reveal that school principals act as transformational leaders who not only manage school administration but also foster a culture of quality, encourage teacher professionalism, and create a conducive learning environment. On the other hand, teachers’ motivation both intrinsic and extrinsic plays a decisive role in keeping the learning process engaging, innovative, and student-centered. The synergy between these two factors has been proven to sustain and even enhance students’ academic achievement over the years. This study emphasizes that leadership strategies and teacher motivation are inseparable in maintaining educational quality. The findings are expected to provide practical contributions for school principals, teachers, and policymakers in formulating sustainable strategies to preserve academic achievement in primary schools